Genome-wide identification and characterization of LcCCR13 reveals its potential role in lignin biosynthesis in Liriodendron chinense - Li, Wei; Hao, Ziyuan; Yang, Lichun; Xia, Hui; Tu, Zhonghua; Cui, Zhengkun; Wu, Junpeng; Li, Huogen (Frontiers in Plant Science, 2023)
Wood formation is closely related to lignin biosynthesis. Cinnamoyl-CoA reductase (CCR) catalyzes the conversion of cinnamoyl-CoA to cinnamaldehydes, which is the initiation of the lignin biosynthesis pathway and a crucial point in the manipulation of associated traits. Liriodendron chinense is an economically significant timber tree. Nevertheless, the underlying mechanism of wood formation in it remains unknown; even the number of LcCCR family members in this species is unclear. This study aimed to perform a genome-wide identification of genes(s) involved in lignin biosynthesis in L. chinense via RT-qPCR assays and functional verification. Altogether, 13 LcCCR genes were identified that were divided into four major groups based on structural and phylogenetic features. The gene structures and motif compositions were strongly conserved between members of the same groups. Subsequently, the expression patterns analysis based on RNA-seq data indicated that LcCCR5/7/10/12/13 had high expression in the developing xylem at the stem (DXS). Furthermore, the RT-qPCR assays showed that LcCCR13 had the highest expression in the stem as compared to other tissues. Moreover, the overexpression of the LcCCR13 in transgenic tobacco plants caused an improvement in the CCR activity and lignin content, indicating that it plays a key role in lignin biosynthesis in the stems. Our research lays a foundation for deeper investigation of the lignin synthesis and uncovers the genetic basis of wood formation in L. chinense.